Plasma protein electrophoresis of Trachemys scripta and Iguana iguana - Giménez, Mercè (Veterinary clinical pathology, 2010)
BACKGROUND: Protein electrophoresis is widely applied in veterinary medicine, but is not used often in reptiles, in part because of lack of reference values